E2Fs co-participate in cadmium stress response through activation of MSHs during the cell cycle - Zheng, Wen-Jie; Li, Wang-Qing; Peng, Yan; Shao, Ye; Tang, Li; Liu, Ci-Tao; Zhang, Dan; Zhang, Lan-Jing; Li, Ji-Huan; Luo, Wu-Zhong; Yuan, Zhi-Cheng; Zhao, Bing-Ran; et al. (Frontiers in Plant Science, 2022)
Cadmium is one of the most common heavy metal contaminants found in agricultural fields. MutSα, MutSβ, and MutSγ are three different MutS-associated protein heterodimer complexes consisting of MSH2/MSH6, MSH2/MSH3, and MSH2/MSH7, respectively. These complexes have different mismatch recognition properties and abilities to support MMR. However, changes in mismatch repair genes (OsMSH2, OsMSH3, OsMSH6, and OsMSH7) of the MutS system in rice, one of the most important food crops, under cadmium stress and their association with E2Fs, the key transcription factors affecting cell cycles, are poorly evaluated. In this study, we systematically categorized six rice E2Fs and confirmed that OsMSHs were the downstream target genes of E2F using dual-luciferase reporter assays. In addition, we constructed four msh mutant rice varieties (msh2, msh3, msh6, and msh7) using the CRISPR-Cas9 technology, exposed these mutant rice seedlings to different concentrations of cadmium (0, 2, and 4 mg/L) and observed changes in their phenotype and transcriptomic profiles using RNA-Seq and qRT-PCR. We found that the difference in plant height before and after cadmium stress was more significant in mutant rice seedlings than in wild-type rice seedlings. Transcriptomic profiling and qRT-PCR quantification showed that cadmium stress specifically mobilized cell cycle-related genes ATR, CDKB2;1, MAD2, CycD5;2, CDKA;1, and OsRBR1. Furthermore, we expressed OsE2Fs in yeasts and found that heterologous E2F expression in yeast strains regulated cadmium tolerance by regulating MSHs expression. Further exploration of the underlying mechanisms revealed that cadmium stress may activate the CDKA/CYCD complex, which phosphorylates RBR proteins to release E2F, to regulate downstream MSHs expression and subsequent DNA damage repairment, thereby enhancing the response to cadmium stress.